Evaluation of mechanical and tribological characteristics of hot-pressed self-lubricating CuO/MgO/ZTA ceramic composites. (2022) - Sajid Hussain, Md; Goswami, Sourav; Ghosh, Kunal; Kumar, Prakash; Mandal, Nilrudra
Abstract: The current study investigates the behavior of hot-pressed copper oxide (CuO) incorporated magnesia-zirconia toughened alumina (MgO/ZTA) ceramic composites. Different compositions of nano CuO and MgO/ZTA were mixed by ball milling and consolidated via hot-press sintering in order to study the change in mechanical properties i.e., fracture toughness, microhardness, and tribological properties i.e., friction coefficient, specific wear rate. Self-lubricating characteristics of the developed composites were investigated against tungsten carbide (WC) ball through ball-on-disc tribometer setup. The addition nano CuO to some extent led to significant improvement in friction coefficient and specific wear rate with the sacrifice of micro hardness property. X-ray diffraction (XRD) clearly shows the presence of CuO phases on the worn surfaces of sintered samples. FESEM images confirmed the formation of smooth patchy layers of nano CuO on the worn wear track of CuO incorporated MgO/ZTA sample by virtue of which both friction coefficient and specific wear rate were reduced significantly. The composition with 1 wt% CuO exhibited the lowest friction coefficient (∼11.76%) and specific wear rate (∼70.77%) values among all the compositions.